2011
DOI: 10.1111/j.1365-2702.2010.03621.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a structured learning programme as a component of the clinical practicum in final year bachelor of nursing programme: a pre–post‐test analysis

Abstract: Nurse educators should not assume that students are less anxious about their acute care clinical placements as the semester proceeds. There is a typical correlation between increased anxiety and decreased self-efficacy which is likely to impact on student learning in the clinical setting. Significant results can be achieved with a relatively low cost and a low technology enabling intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…The results point to preferential implementation scenarios namely, college (10)(11)(13)(14)(15)(16)(18)(19)(20)22,25) and the clinical context (8,9,12,17,21,(23)(24)(25) , according to the purpose of the studies undertaken and the need to control or not the analyzed variables. The type of pedagogical strategy adopted is conditioned by the place where it is undertaken to the limitations and constraints imposed by these means.…”
Section: Pedagogical Strategies That Promote Collaboration and Teamworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The results point to preferential implementation scenarios namely, college (10)(11)(13)(14)(15)(16)(18)(19)(20)22,25) and the clinical context (8,9,12,17,21,(23)(24)(25) , according to the purpose of the studies undertaken and the need to control or not the analyzed variables. The type of pedagogical strategy adopted is conditioned by the place where it is undertaken to the limitations and constraints imposed by these means.…”
Section: Pedagogical Strategies That Promote Collaboration and Teamworkmentioning
confidence: 99%
“…Removal of the duplicate n=139 The students of the first cycle of Nursing studies, as the main participants, were assumed in all of them, with a greater predominance of those who attended the last year (n=7) (10)(11)(12)(13)(14)(15)18,23) . This distinction is justified by the fact that in the last year of the course students already hold knowledge and skills acquired previously, which gives them the necessary maturity for the later acquisition of the capacity to collaborate and work in teams (11) .…”
Section: Final Articles Of the Integrative Literature Review N=18mentioning
confidence: 99%
See 1 more Smart Citation
“…Granero-Molina et al [20] reported that students participating in their program had reduced levels of stress in the clinical environment. Similarly Watt et al [21] reported that students in their program had reduced levels of anxiety and increased self-efficacy in the clinical environment. Ünal [22] found that a self-awareness and communication techniques program developed improved self-esteem and assertiveness in nursing students.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Stress can inhibit learning and performance [15] , and students perceive clinical stressors more acutely than academic or external stressors. Student anxiety has a negative effect on their ability to learn in the clinical environment [16] . Burnett [17] concludes that successful transition to the first year of study increases student satisfaction with their program and is an important factor in academic and career attrition.…”
Section: Background Of the Studymentioning
confidence: 99%